Capped Plasmonic Gold and Silver Nanoparticles with Porphyrins for Potential Use as Anticancer Agents-A Review - Nthabeleng Hlapisi; Sandile P. Songca; Peter A. Ajibade (MDPI AG, 2024)
Photothermal therapy (PTT) and photodynamic therapy (PDT) are potential cancer treatment methods that are minimally invasive with high specificity for malignant cells. Emerging research has concentrated on the application of metal nanoparticles encapsulated in porphyrin and their derivatives to improve the efficacy of these treatments. Gold and silver nanoparticles have distinct optical properties and biocompatibility, which makes them efficient materials for PDT and PTT. Conjugation of these nanoparticles with porphyrin derivatives increases their light absorption and singlet oxygen generation that create a synergistic effect that increases phototoxicity against cancer cells. Porphyrin encapsulation with gold or silver nanoparticles improves their solubility, stability, and targeted tumor delivery. This paper provides comprehensive review on the design, functionalization, and uses of plasmonic silver and gold nanoparticles in biomedicine and how they can be conjugated with porphyrins for synergistic therapeutic effects. Furthermore, it investigates this dual-modal therapy's potential advantages and disadvantages and offers perspectives for future prospects. The possibility of developing gold, silver, and porphyrin nanotechnology-enabled biomedicine for combination therapy is also examined.